Modal Preference in Ho Chi Minh City, Vietnam: An Experiment With New Modes of Transport. (April 2019) - Nguyen, Duy Chinh; Hoang, Huu Dung; Hoang, Huu Tien; Bui, Quang Trung; Nguyen, Lan Phuong
An overwhelming majority of inhabitants in Ho Chi Minh City use motorbike as their primary means of transport, causing severe urban traffic congestion. As an effort to combat congestion, the local and central government started constructing the first urban railway line (metro) in 2009. In this study, travel demand for different modes of transport was investigated using discrete choice experiment. In addition to conventional choices such as motorbike and bus, we included new technology-assisted taxi service and the first urban railway (Ben Thanh–Suoi Tien) as a hypothetical choice. The data set contains 267 respondents spanning 19 communes across the railway. The results pointed out that mode choice is influenced by both total travel time and total travel cost. The findings also highlighted the importance of transiting time and transiting cost in public transports. In terms of welfare, metro users are willing to pay 976 and 667 VND for a minute reduction of transiting time and transporting time, respectively. When a motorbike user switches to metro mode, monetary welfare of that individual rises by approximately 56, 000 VND.